The Relationship of Community’s Participation with The Sustainability of Ecology, Sosio-Culture and Economic in Marine Ecotourism - Utami, Putri Ria; Mardiana, Rina (Departemen Sains Komunikasi dan Pengembangan Masyarakat, Fakultas Ekologi Manusia, IPB, 2017)
Community’s participation in marine ecotourism potential is important because people have the landscape and culture potential sale value as marine ecotourism attraction. The purpose of this study was to analyze the relation of community’s participation with sustainability of ecology, socio-culture and economic life of local communities in marine ecotourism Pahawang Island. This research was a quantitative research with survey method, supported by qualitative data. The number of samples in this study was 50 respondents, which cosists of the member participants in marine ecotourism Pahawang Island. The results showed that community’s participation level has medium correlation and significant relation to sustainability’s of ecology level and sustainability’s of socio-culture level. While, community’s participation level shows a very strong correlation and significant relation to sustainability’s of economic level. Keywords : ecology sustainability, economic, marine ecotourism, participation, socio-culture================================================== ABSTRAKPartisipasi aktif dari masyarakat dalam mengelola potensi ekowisata bahari sangat penting karena bentang alam dan potensi budaya memiliki nilai jual sebagai daya tarik ekowisata bahari. Penelitian ini bertujuan untuk menganalisis hubungan partisipasi masyarakat terhadap keberlanjutan ekologi, sosial-budaya dan ekonomi masyarakat setempat dalam ekowisata bahari Pulau Pahawang. Penelitian ini adalah penelitian kuantitatif yang menggunakan metode survey dengan didukung data kualitatif. Jumlah sampel penelitian sebanyak 50 responden yang merupakan pengelola ekowisata bahari Pulau Pahawang. Hasil penelitian menunjukkan tingkat partisipasi masyarakat terhadap tingkat keberlanjutan ekologi dan tingkat keberlanjutan sosial-budaya menunjukkan hubungan cukup dan signifikan. Sedangkan, tingkat partisipasi masyarakat memiliki hubungan kuat dan signifikan terhadap tingkat keberlanjutan ekonomi.Kata Kunci : ekonomi, ekowisata bahari, keberlanjutan ekologi, sosial-budaya, partisipasi